Fenomena Trash-Talk dalam Game Online Mobile Legends: Bang Bang (Studi Kasus pada Mahasiswa Universitas Mulawarman) - Fransisca Corry Famelia; Ainun Ni`matu Rohmah; Johantan Alfando Wikandana Sucipta; Harry Isra Muhammad (Cerdika: Jurnal Ilmiah Indonesia, 2026)
The advancement of internet technology has significantly increased the popularity of online games as a source of entertainment across different age groups, particularly among university students. One of the most popular games is Mobile Legends: Bang Bang (MLBB), a Multiplayer Online Battle Arena (MOBA) game that not only prioritizes competitive gameplay but also facilitates interaction and communication among players. Within these interactions, trash-talk frequently occurs, referring to verbal expressions such as taunts, sarcasm, and the use of offensive language during gameplay. This study seeks to explore and describe the phenomenon of trash-talk in Mobile Legends: Bang Bang among students of Mulawarman University in Samarinda, East Kalimantan.This research adopts a qualitative approach using a descriptive method. Data were obtained through in-depth interviews with Mulawarman University students who actively engage in playing Mobile Legends: Bang Bang. The data were then analyzed qualitatively through an inductive approach to identify the forms, meanings, and contributing factors associated with the emergence of trash-talk in the game. The results reveal that trash-talk has become an integral part of gaming culture and is generally perceived as a normal practice by players. Players engage in trash-talk for various reasons, including emotional expression, responding to provocation, strengthening team solidarity, and employing psychological tactics to distract opponents. The identified forms of trash-talk include the use of harsh language, ridicule of players’ performance, sarcasm, and indirect mockery, which may be directed toward both opponents and teammates. The anonymity provided by online gaming environments further facilitates such behavior and, in certain instances, involves discriminatory elements